A shape-reconfigurable electronic composite for stimulus customizable detection via neutral plane shifting - Gong, Dohyeon; Roh, Yeonwook; Lee, Jae Hyun; Hwang, Suhyeon; Kim, Changhwan; Ji, Kyungbin; Kwon, Gibeom; Back, Inryeol; Shin, Dongwook; Lim, Daseul; Hong, Insic; Lee, Doohoe; et al. (Materials Horizons, 2024)
Three-dimensional (3D) sensors selectively measure the applied force in a particular direction through the designed shape. However, such a fixed sensor design incurs a relatively lowsensitivity and narrowmeasurement range to forces applied from other directions. Here, we report a shapereconfigurable electronic composite based on a stiffness-tunable polymer and a crack-based strain sensor. The stiffness-tunable polymer allows a high degree of freedom (DOF) in modifying the shape of the electronic composite in its flexible state, enabling the formation of various 3D structures. This modification involves shifting the neutral plane toward the electrode to prevent fractures in the embedded sensors. After modifying the shape of the soft and flexible electronic composite, the dramatically increased stiffness of the stiffness-tunable polymer enables the maintenance of the reconfigured shape of the electronic composite and amplifies the mechanical signal from the external force of the targeted direction by returning the neutral plane to the original position. We validated the reversible modification of the shape of the electronic composite by demonstrating the increase in sensitivity and measured range for targeted external forces (bending, pressing, and stretching) via sequential changes in the designed shapes (wire, spiral, and spring) compared to the initial shape. This facile approach for shape modification will provide an opportunity to realize versatile shape changes in rigid electronics for user purpose.
Keywords: Applied forces; Customizable; Electronic composites; External force; Low sensitivity; Neutral plane; Reconfigurable; Sensor designs; Three-dimensional sensor; Tunables